2021
DOI: 10.21608/mjae.2021.54351.1018
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of Pomegranate Seeds Drying Unit Using Infrared / Hot Air Dryer

Abstract: In the present study combined infrared and hot air dryer to dry a thin layer of pomegranate seeds. Three different levels of infrared power, namely: 200, 250 and 300 W and three different exposure distance "the distance between infrared heater and samples" of dying are 20, 15 and 10 cm with air temperature 40 o C and air velocity 1.5 m/s were studied. Drying time as affected by infrared power and exposure distance, compatibility of experimental data to some drying models, effective diffusivity "Deff", rehydrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Taghinezhad et al (2021) observed the effective moisture diffusivity values of 1.007 × 10 −9 to 8.1110 −9 m 2 /s during drying of turnip slices in a hybrid convective‐IR dryer. D eff values of pomegranate seeds in a combined IR and hot air dryer were ranged between 0.15 × 10 −7 and 1.57 × 10 −7 m 2 /s (Eissa, 2021).…”
Section: Drying Kinetics Of Food Materials In Ir and Ir‐assisted Dryingmentioning
confidence: 99%
See 1 more Smart Citation
“…Taghinezhad et al (2021) observed the effective moisture diffusivity values of 1.007 × 10 −9 to 8.1110 −9 m 2 /s during drying of turnip slices in a hybrid convective‐IR dryer. D eff values of pomegranate seeds in a combined IR and hot air dryer were ranged between 0.15 × 10 −7 and 1.57 × 10 −7 m 2 /s (Eissa, 2021).…”
Section: Drying Kinetics Of Food Materials In Ir and Ir‐assisted Dryingmentioning
confidence: 99%
“…W. P. Zhang, Chen, et al (2020) developed a new pilot-scale pulsed vacuum IR drying system for the drying of berries and recommended this as a promising method to produce high-quality dried berries. Eissa (2021) studied the effect of IR power (200, 250, and 300 W), the distance between IR heater and samples (20, 15, and 10 cm), air temperature (40 C) and air velocity (1.5 m/s) on thin-layer drying of pomegranate seeds in a combined IR and hot air dryer and reported the least drying time of 40 min at IR power of 300 W and exposure distance of 10 cm. Dolgun, Aktas ¸, and Dolgun (2021) designed an IRassisted heat pump dryer with heat recovery to reduce the energy consumption during walnut drying and reported the energy efficiency between 0.29% and 7.94% which is 10% higher energy savings and 20% time savings than heat pump drying.…”
Section: Introductionmentioning
confidence: 99%
“…the energy of radiation penetrates through the material and is converted into heat Moisture is removed from the inner body (Swasdisevi et al, 2009). Infrared radiation has been applied in conjunction with several drying processes because it has advantages of increasing the drying efficiency , dried product quality is generally reported to be higher Several researchers have applied IR-assisted drying successfully to many food products, In addition the advantages of Infrared radiation, IR are energy savings, lower drying time, intermittent energy source, uniform temperature distribution, friend of the environment, and reduce the space (Eissa, 2021). The effect of microwave power air velocity and temperature on the final drying of bananas observed that increasing the drying rate by microwave power increased, thus making the drying time shorter (Omolola et al, 2015).…”
Section: Introductionmentioning
confidence: 99%